2020
DOI: 10.1029/2020jd033455
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Meteorological to Hydrological Droughts in India

Abstract: Drought is among the costliest natural disasters that affect the economy, food and water security, and socioeconomic well-being of about 1.4 billion people in India. Despite the profound implications of droughts, the propagation of meteorological to hydrological droughts in India is not examined. Here, we use observations and simulations from a well-calibrated and evaluated Variable Infiltration Capacity (VIC) model to estimate drought propagation in India. Standardized Precipitation Index (SPI), Standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 80 publications
(188 reference statements)
0
32
0
Order By: Relevance
“…Bhardwaj et al. (2020) used standardized precipitation evapotranspiration index and SSI to study meteorological drought and hydrological drought in India, and showed that hydrological drought lagged behind meteorological drought by 1–3 months. Zhou, Shi, et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bhardwaj et al. (2020) used standardized precipitation evapotranspiration index and SSI to study meteorological drought and hydrological drought in India, and showed that hydrological drought lagged behind meteorological drought by 1–3 months. Zhou, Shi, et al.…”
Section: Discussionmentioning
confidence: 99%
“…VIC hydrological model has been used earlier for analysing the impact of land use land cover change (Aggarwal et al 2012;Garg et al 2017;Garg et al 2019), climate change (Aggarwal et al 2016;Garg et al 2013, Sharma et al 2020) on hydrology of river basins. It is also being used to simulate hydrological processes for assessment, characterisation and evolution of droughts (Bhardwaj et al 2020;Mishra et al 2010;Niu et al 2015;Shamshirband et al 2020). VIC, a grid-based land surface representation model simulates land surfaceatmosphere fluxes of moisture and energy.…”
Section: Hydrological Modelling Of Godavari Basinmentioning
confidence: 99%
“…Over the last decade, the propagation of meteorological drought to another form of droughts has been a significant topic in the hydrological research community (Barker et al 2016;Nanda et al 2021;Van Loon and Laaha 2015;Wang et al 2021) but with only one peer-reviewed study (Bhardwaj et al 2020) available for Indian region. Detailed investigation examining-How the meteorological drought induced by the climatic anomalies develops and propagates considering the anthropogenic interventions is required for Indian river basins.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of all droughts starts from lack of precipitation (meteorological drought). It gradually spreads to the other sectors in the form of deficiency in soil moisture (agricultural drought) and reduction of surface water and groundwater resources (hydrological drought) (Bhardwaj et al 2020, Huang et al 2017, Van Lanen 2006. Therefore, the accurate monitoring of meteorological drought would be very important in predicting agricultural and hydrological droughts.…”
Section: Introductionmentioning
confidence: 99%